2022
DOI: 10.1371/journal.pone.0273540
|View full text |Cite
|
Sign up to set email alerts
|

On the surface or down below: Field observations reveal a high degree of surface activity in a burrowing crayfish, the Little Brown Mudbug (Lacunicambarus thomai)

Abstract: Opposed to most crayfish species that inhabit permanent bodies of water, a unique burrowing lifestyle has evolved several times throughout the crayfish phylogeny. Burrowing crayfish are considered to be semi-terrestrial, as they burrow to the groundwater—creating complex burrows that occasionally reach 3 m in depth. Because burrowing crayfishes spend most of their lives within their burrow, we lack a basic understanding of the behavior and natural history of these species. However, recent work suggests that bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Primary burrowing crayfish spend most of their life in elaborate burrows disconnected from running, oxygenated waters, from which they emerge for mating and food foraging [ 17 , 57 ]. Even though these burrows contain an air/water interface, conditions inside the flooded portions of these burrows are harsh: the dissolved oxygen levels might reach as low as 0.7 mg/L and a pH below 4.5 [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary burrowing crayfish spend most of their life in elaborate burrows disconnected from running, oxygenated waters, from which they emerge for mating and food foraging [ 17 , 57 ]. Even though these burrows contain an air/water interface, conditions inside the flooded portions of these burrows are harsh: the dissolved oxygen levels might reach as low as 0.7 mg/L and a pH below 4.5 [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that conspicuous colouration in crayfish is evolutionarily correlated to a semi-terrestrial burrowing strategy. Therefore, the typical association between light environment and adaptive colouration lacks support based on the reclusive lifestyle of semi-terrestrial burrowing crayfishes because semi-terrestrial burrowing species are nocturnal and rarely interact with each other on the surface [83]. Thus, two major questions remain unresolved: why conspicuous colours would be more common in species that rarely leave their burrow and are nocturnal, and are there costs and benefits to these conspicuous colours?…”
Section: Discussionmentioning
confidence: 99%
“…We found that conspicuous coloration in crayfish is evolutionary correlated to a semi-terrestrial burrowing strategy. Therefore, the typical association between light environment and adaptive coloration lacks support based on semi-terrestrial burrowing crayfish's reclusive lifestyle; because semi-terrestrial burrowing species are nocturnal and based on current knowledge, rarely interact with each other on the surface (Diehl et al, 2022). Thus, major questions remain unresolved, for example: why would conspicuous colors be more common in species that rarely leave their burrow and are nocturnal?.…”
Section: Discussionmentioning
confidence: 99%